2020
DOI: 10.1155/2020/9738567
|View full text |Cite
|
Sign up to set email alerts
|

Association Study of Coronary Artery Disease-Associated Genome-Wide Significant SNPs with Coronary Stenosis in Pakistani Population

Abstract: Genome-wide association studies (GWAS) of coronary artery disease (CAD) have revealed multiple genetic risk loci. We assessed the association of 47 genome-wide significant single-nucleotide polymorphisms (SNPs) at 43 CAD loci with coronary stenosis in a Pakistani sample comprising 663 clinically ascertained and angiographically confirmed cases. Genotypes were determined using the iPLEX Gold technology. All statistical analyses were performed using R software. Linkage disequilibrium (LD) between significant SNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…In addition to the SNPs at the 1p13.3 CELSR2-PSRC1-SORT1 locus being strongly associated with circulating LDL-C levels, this locus is also associated with several contributors of CAD, including atherosclerosis and arterial calcification ( 17 , 18 , 229 , 244 , 246 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 , 291 , 292 , 293 ). While LDL-C is a major risk factor for atherosclerosis, studies have found that sortilin may play a role in the development of atherosclerosis independent of its effect on circulating LDL-C levels.…”
Section: The Role Of Sortilin In Cardiovascular and Metabolic Diseasementioning
confidence: 99%
“…In addition to the SNPs at the 1p13.3 CELSR2-PSRC1-SORT1 locus being strongly associated with circulating LDL-C levels, this locus is also associated with several contributors of CAD, including atherosclerosis and arterial calcification ( 17 , 18 , 229 , 244 , 246 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 , 291 , 292 , 293 ). While LDL-C is a major risk factor for atherosclerosis, studies have found that sortilin may play a role in the development of atherosclerosis independent of its effect on circulating LDL-C levels.…”
Section: The Role Of Sortilin In Cardiovascular and Metabolic Diseasementioning
confidence: 99%
“…SNF8 , UBE2Z , CALCOCO2 , and ATP5MC1 have been shown a core function in metabolic disease and cancer. Partial QTLs or SNPs have been associated with coronary artery disease ( SNF8 and UBE2Z ) [ 54 , 55 ]. CALCOCO2 is associated with autophagy-related genes, influencing tumorigenesis and progression of osteosarcoma [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…51 Furthermore, in Pakistani populations, no associations were detected between this Single Nucleotide Polymorphism (SNP) and CAD or lipid parameters. 52 Besides CAD, stroke is another clinical manifestation of atherosclerosis. Association of MRAS with atherosclerotic stroke was observed in a Han Chinese population including 202 patients and 188 controls.…”
Section: Mras Risk Variants For Atherosclerosis Cad and Strokementioning
confidence: 99%
“…In Czeck Slavonic population, rs9818870 was not associated with acute coronary syndrome or mortality 51 . Furthermore, in Pakistani populations, no associations were detected between this Single Nucleotide Polymorphism (SNP) and CAD or lipid parameters 52 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation